Technology enhanced learning for people with disabilities : approaches and applications - Ordonez de Pablos, Patricia, 1975-; Zhao, Jingyuan, 1968-; Tennyson, Robert D. (Hershey, PA : Information Science Reference, 2011)
'This book brings together academics, policy-makers and practitioners, with the goal of delivering a reference edition for all those interested in approaches and applications of technology enhanced learning for people with disabilities'--Provided by publisher.
Includes bibliographical references (p. 203-224) and index.
Keywords: Students with disabilities -- Computer-assisted instruction; Computers and people with disabilities; Educational technology